Religious Spirituality: Sufi Healing for Rehabilitation of Juvenile Delinquency - Santoso, Try Riduwan; Salahudin, Asep; Salam, Faiz Abdul; Kafiul Khuluq, Muhammad Shahinshah; Suryana, Nana (Pascasarjana IAIN Pontianak, 2024)
Sufi Healing therapy is a spiritual or non-medical therapy which is conducted through Sufi practices during the suluk process. The purpose of this paper is to discuss the manner in which Sufi Healing model is applied in the process of reforming juvenile delinquents. In this study, the description of the data is qualitative which has been collected through observations, interviews and documentation. This study has shown that there is a Sufi Healing model in rehabilitating the juvenile delinquents at the Rehab Center employing Sufi tradition through rituals. According to the Sufi Healing model, the following are the factors; Doctrine of tariqa teachings, Murshid [mentor] and Coach. The prescriptions for the juvenile delinquents in Sufi Healing aim to improve self-awareness and personal self-control. The Sufi Healing ritual is also capable of making the pious individually and socially positive of adolescents who have such personalities, as well as enhance human consciousness and self-governance to perform positive actions. This paper established that Sufi Healing is an example of an alternative model of therapy for rehabilitation of juvenile delinquency based on spirituality. From this research, it is recommended that mental health remains a central control and command point in people’s lives.